The analysis of single nucleotide polymorphisms of the DGCR8 and XPO5 genes, and their association with the incidence of primary open angle glaucoma - Molasy, Milena; Walczak, Anna; Przybyłowska-Sygut, Karolina; Szymanek, Katarzyna; Szaflik, Jerzy; Szaflik, Jacek P.; Majsterek, Ireneusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Purpose : To analyse the single nucleotide polymorphisms of DGCR8 and XPO5 genes, involved in miRNA processing pathway, in relation to the incidence of primary open-angle glaucoma. Material and methods : Blood samples as the biological material used for the experiment were voluntarily donated by patients with known primary open-angle glaucoma and age-matched healthy controls. The two control groups – rs3757 DGCR8 and rs11077 XPO5 – consisted of 135 and 140 volunteers, respectively. The two study groups – rs3757 DGCR8 and rs11077 XPO5 – consisted of 137 and 138 subjects, respectively. The polymorphic variant frequencies of rs3757 and rs1107 were determined using DNA isolated from the peripheral blood lymphocytes in TaqMan® SNP Genotyping Assays. Results : The statistical analysis revealed that the genotype AG of DGCR8 rs3757 occurred more frequently in healthy individuals (P = 0.001), while homozygote GG was present mostly in people affected by primary open-angle glaucoma (P = 0.003). No association between the risk of primary open angle glaucoma and AC/CC genotypes of XPO5 was found. Conclusion : Many reports suggest the association between the miRNA alteration and the pathogenesis of glaucoma. The single nucleotide polymorphisms in DGCR8 and XPO5 genes, involved in microRNA biogenesis, may be the key factor in this process. Our experiment showed that genotype AG in rs3757 DGCR8 exhibits protective effect, decreasing the risk of primary open angle glaucoma, while the homozygote GG is probably associated with increased risk of glaucoma. The analysis of polymorphic variants of the genes involved in miRNA biogenesis could enable identification of glaucoma high-risk groups.